-3t(-7-3)+2t-23=0

Simple and best practice solution for -3t(-7-3)+2t-23=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3t(-7-3)+2t-23=0 equation:


Simplifying
-3t(-7 + -3) + 2t + -23 = 0

Combine like terms: -7 + -3 = -10
-3t(-10) + 2t + -23 = 0

Reorder the terms for easier multiplication:
-3 * -10t + 2t + -23 = 0

Multiply -3 * -10
30t + 2t + -23 = 0

Reorder the terms:
-23 + 30t + 2t = 0

Combine like terms: 30t + 2t = 32t
-23 + 32t = 0

Solving
-23 + 32t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '23' to each side of the equation.
-23 + 23 + 32t = 0 + 23

Combine like terms: -23 + 23 = 0
0 + 32t = 0 + 23
32t = 0 + 23

Combine like terms: 0 + 23 = 23
32t = 23

Divide each side by '32'.
t = 0.71875

Simplifying
t = 0.71875

See similar equations:

| -28=-4/5d | | 2bitch-1bitch= | | 4(r-4)+12r=0 | | 2(4x+16)=18 | | 25+4u=65 | | -12x+8x-4=-4(x+1) | | 3n^2-13n=10 | | 5k-9/4=3 | | 8x-72=-8x+40 | | 14m-5(m-2)+26=0 | | -31-4x=-10(1+5x) | | 3+4b-14=15-5b-4b | | 4y+3x=1368 | | h(t)=-2t^2+12t-11 | | (17x+8)-5=20 | | 3y+4x=1368 | | 5x/2-4=5 | | 3+4b-14=15-5b-4bford | | -(x+2)+5x=6x+14 | | h(t)=-2t^12f+11 | | g+g+2=1000 | | x+45+6x-5=180 | | 5x^2-6x+7+8x+4+5x^2= | | 4e(2x+1)=20 | | -2x/-1 | | 3a+5b=63 | | 5/11t=7(5-2t) | | sin(x)=0.857633 | | -x^2/-1 | | 0.72x=7.5 | | N-17=4(1-5n) | | 3(x-7)/2=15 |

Equations solver categories